The 1996 Mahakali Treaty: Whither the “Rashtriya Sankalpas/National Strictures” of Nepalese Parliament? - Pun, Sant Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Despite the ratification by the Joint Session of Nepal’s two Houses of Parliament with an overwhelming majority on September 20, 1996 and despite the exchange of instruments of ratification by the two countries on June 5, 1997, the Pancheshwar Detailed Project Report (DPR) has yet to see the light of day even after the lapse of 16 years. It was believed that Prime Minister Sher Bahadur Deuba’s government with the concurrence of the main opposition party, Communist Party of Nepal- United Marxist Leninist (CPN-UML), had ratified the Mahakali Treaty with four ‘rashtriya sankalpas/national strictures’. It was also believed that an all party Parliamentary Monitoring Joint Committee headed by the Speaker of the Lower House was constituted to guide the Nepalese side in the preparation of the detailed project report of Pancheshwar. That Monitoring Joint Committee in a span of four years held 28 meetings. Now the very legality of those four ‘rashtriya sankalpas/national strictures’ is being questioned. In 2009 the Secretary level Nepal-India Joint Committee on Water Resources constituted the Pancheshwar Development Authority (PDA) that was given the crucial mandate to ‘finalize’ the vital much-awaited Pancheshwar DPR. As institutions have no memory and public memory is extremely short, this article attempts to recapitulate the commitments made at treaty ratification time by the Deuba government in concurrence with the then largest party, CPN-UML. The article argues against the mandate given to the bureaucrat-led PDA to finalize the Pancheshwar DPR and strongly recommends formation of an all party mechanism akin to the previous Parliamentary Monitoring Joint Committee to guide the government during this critical Interim period. DOI: http://dx.doi.org/10.3126/hn.v11i0.7155 Hydro Nepal Vol.11 2011 pp.12-17